Communities’ socio-economic status and environmental conservation behaviour in marine protected areas : A study of Malaysia / Muhammad Mehedi Masud - Masud, Muhammad Mehedi (2015)
Environmental degradation creates adverse impacts on lives, livelihoods, development of human society and conservation of natural resources especially, for marine protected areas. This study examines the establishment of Marine Protected Areas (MPAs) in Malaysia with specific reference to the Tioman Island Marine Park, The Redang Islnad Marine Park and the Tinggi Island Marine Park off the east coast of Peninsular Malaysia. This study investigated the communities’ wellbeing, their perception on socio-economic development and environmental conservation behaviour (ECB) to recommend an integrated effective management policy framework. In order to achieve the objective of this study, mixed methods were applied. Qualitative method was conducted based on Focus Group Discussion (FGD) and quantitative based on survey questionnaire. After collecting the data, all the statistical analyses were carried out using Statistical Package for the Social Science (SPSS) (22.0 version) and Analysis of Moment Structures (AMOS) (22.0 version). Specifically, SPSS is used for analysing the statistics, testing of assumptions for normality, reliability, exploratory factor analysis and multiple regression analysis. AMOS is used for confirmatory factor analysis (CFA) and full-fledged structural equation modelling (SEM). The study revealed that Marine Park Community identified several vulnerability context to marine park community livelihoods, for instance, price hike for essential goods as the most important problem within MPAs, followed by the increase in waste generation by restaurants and tourists, the quality of water dropped, drought, heat and haze due to climate change and changing their occupation after the establishment of the MPA from fishing to other professions. From the findings of this study, we determined that the local community’s standard of living has important in terms of physical and social assets; but they have a substantial lack of human, financial and environmental iv assets. One of the main attributes of human assets is a community’s education level, yet this study shows that a significant number of respondents do not have formal education. This study found that socioeconomic factors have positive significant impact on environmental awareness, attitudes towards sustainable use of marine resources, and perceived impact of socioeconomic development. This study also revealed that perceived development of human capital (PHCD), perceived development of social capital (PSCD), perceived development of financial capital (PFCD) have greater significant influence on environmental awareness and attitudes and environmental conservation behaviour. It also indicated that environmental awareness and attitudes can play mediating role between perceived socio-economic development and environmental conservation behaviour. Finally, this study found that there is lack of effective management policy framework for management of marine resources. Hence, this study recommended an integrated management policy framework considering social, economic development, environmental issues, management issues and psychosocial factors for the socio-economic development of the local community and conservation of marine resources within MPAs. Therefore, this study will help policy makers to formulate better policies for conserving marine diversity, as well as to improve the socio-economic status of the local community.